The Silk Road: The Spread and Acculturation of Buddhist Art and Architecture - Crump, Ezra (2025)
This work will examine the extent of the acculturation of Buddhist art and architecture as the religion spread along the ‘Silk Road’, focussing upon the regions of ancient Gandhāra in modern-day Pakistan and Afghanistan, and Dunhuang in the modern-day Gansu province of China. It will discuss three case studies, the site of Jamālgarhī in Gandhāra, and Cave 257 and Cave 275 at the site of the Mogao Caves at Dunhuang. Within these case studies, the focus will be on their architecture, including the key Buddhist monument of the ‘stūpa’, in addition to a Buddha image and depictions of stories and scenes from the Dharma, demonstrating that the acculturation of Buddhism within these disparate regions did indeed result in composite visual languages, admixing with the existing architectural and artistic traditions. Given the importance of images within Buddhism, allowing for the spread of key concepts and stories without the need for translation or literacy, the presence of new cultural influences within Buddhist material culture can therefore be seen as a reflection of the acculturation of Buddhism and Buddhist communities as the religion spread along the ’Silk Road'.